PREVENTING BIAS IN THE BALANCED SCORECARD IMPLEMENTATION FOR PERFORMANCE ASSESSMENT - ARDHANI SISDYANI, EKA (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 2 No 1 (2007))
Balanced scorecard has been widely recognized as a tool of comprehensive performance measurement both for small and large organizations. However, when the method is employed to compare performance of two or more business units, evaluator might encounter with common-measures bias. This bias would emerge when evaluator only pay attention to common measures existed in the units being evaluated, and ignore the unique measures belong to each individual unit. This condition would mislead evaluator to reach inaccurate conclusion regarding the achievement of the units, and consequently could end up with incorrect decision, such as compensation policy. Such a bias can be reduced by employing a technique that has been empirically studied by Roberts, Albright, and Hibbets (2004), called disaggregated plus mechanically aggregated. This technique has successfully reduced common-measures bias presented in the absence of a treatment using this technique.
Keywords: balanced scorecard, common-measure bias, performance